Work First and Forget About Education: New York City's Personal Responsibility Act and the Creation of a Working Underclass - Brown, Delores D. Jones (Social justice, 2001)
Although the New York City Personal Responsibility Act states its intention is to transfer New Yorkers from welfare to self-sufficiency, its real objective is to reduce the welfare rolls, regardless of how that is achieved. Its Work Experience Program (WEP) is not devised to prepare participants for self-sustaining employment, but is instead a mechanism for sustaining their subordinate economic position by engaging them in unskilled and sometimes degrading “work activities” under the pretext of having them work for their benefits. Moreover, the city, rather than the individual, seems to profit from the WEP experience as paid municipal workers are replaced with workfare recipients at little or no cost.